2014
DOI: 10.3389/fncom.2014.00103
|View full text |Cite
|
Sign up to set email alerts
|

Sustained oscillations, irregular firing, and chaotic dynamics in hierarchical modular networks with mixtures of electrophysiological cell types

Abstract: The cerebral cortex exhibits neural activity even in the absence of external stimuli. This self-sustained activity is characterized by irregular firing of individual neurons and population oscillations with a broad frequency range. Questions that arise in this context, are: What are the mechanisms responsible for the existence of neuronal spiking activity in the cortex without external input? Do these mechanisms depend on the structural organization of the cortical connections? Do they depend on intrinsic char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(66 citation statements)
references
References 57 publications
7
53
0
6
Order By: Relevance
“…Our main finding is that the hierarchical and modular topology creates an effect of slow fluctuations, similar to the one created by an increase of synaptic efficacy, which in turn shapes information propagation and processing through those modules. Previous studies have shown that hierarchical and modular networks are advantageous in the sense of activity sustainment [29] and can present critical behaviors [28] that are connected to optimal transmissions [48], here we see that modularity may also create optimal transmission. In particular, this does not necessarily happens due to high magnitude of information transfer, but may happen at a transition point in the level of hierarchical organization which endows a robust communication independently of synaptic strength.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our main finding is that the hierarchical and modular topology creates an effect of slow fluctuations, similar to the one created by an increase of synaptic efficacy, which in turn shapes information propagation and processing through those modules. Previous studies have shown that hierarchical and modular networks are advantageous in the sense of activity sustainment [29] and can present critical behaviors [28] that are connected to optimal transmissions [48], here we see that modularity may also create optimal transmission. In particular, this does not necessarily happens due to high magnitude of information transfer, but may happen at a transition point in the level of hierarchical organization which endows a robust communication independently of synaptic strength.…”
Section: Discussionsupporting
confidence: 66%
“…An interesting question in computational neuroscience has been the investigation of different dynamics achieved by networks composed of spiking neurons [13,44,28,45] and in particular the ones that enhance information processing such as networks embedded in slow fluctuations [27,12,14]. Structural characteristics and how they interact with the dynamics are also of great interest [46,47] and, in this regard, a hierarchical and modular topology faithfully represents generic characteristics of a cortical network [18,20,29]. In this work, we have constructed large-scale networks populated by spiking neurons with increasing levels of hierarchy which we extracted information theory grounded measures.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the Potjans-Diesmann model was successfully replicated in a different 10 platform than the one in which it was originally implemented. 11 2 Introduction 12Most theoretical studies of cortical activity are based on networks of randomly connected units [2,6,7,12] or 13 with architectures artificially built from random networks [10]. In spite of the usefulness of these models, in 14 order to understand the interplay between network structure and cortical dynamics it is essential to have 15 computational models which accurately represent the cortical network architecture.…”
mentioning
confidence: 99%
“…Methods of mean-field analysis, dynamical systems analysis, and information theory were developed and applied. have been published elsewhere (Tomov, Pena, Zaks, & Roque, 2014;Tomov, Pena, Roque, & Zaks, 2016). Using interpretations based on single-neuron and network dynamical systems analyses, we explain why this activity starts and the reason for its eventual complete cessation.…”
Section: Goalsmentioning
confidence: 96%
“…Networks in which the nodes feature more complicated dynamics than LIF neurons and are able to reproduce intrinsic firing patterns of contrasting cortical neurons, e.g. based on the Izhikevich (Izhikevich, 2003(Izhikevich, , 2007 or the AdEx (Brette & Gerstner, 2005;Gerstner et al, 2014) (Tomov et al, 2014(Tomov et al, , 2016. This suggests that not only synaptic balance of excitation/inhibition but also heterogeneities in the neuronal composition of the network may have an impact on the dynamic pattern of the network.…”
Section: Introductionmentioning
confidence: 99%